DESAIN E-MODUL MATA KULIAH SENI TEMBANG MACAPAT BAGI MAHASISWA MBKM LINTAS PROGRAM STUDI - Nur Hasan, Latif; Marsudi,; Retno Utami, Respati; Lani Anggapuspa, Meirina; Alfiranda Zahroh, Adinda (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2023)
Cross-study courses are one of the programs of the Independent Campus Free Learning Curriculum. One of the courses offered across study programs by the Javanese Language and Literature Education Study program is the Macapat Song Arts Course. As a beginner learner in a song course, students will of course experience several problems, namely:1) The tone in the song is different from the tone of modern music (diatonic) which is usually heard and sung. Songs use pentatonic, so adjustments need to be made. 2) There are two types of tunings that students must also master, namely pelog and slendro with a different tone too. 3) Men's and women's voices have different ranges so they require different treatment. 4) the types of cengkok/types of songs in Macapat vary greatly, making it more difficult to memorize. In effort to ensure that students outside the Javanese Language and Literature Education study program need special treatment so that it is easier for them to take courses. Researchers in this case will design an Electronic Module for the Song Arts Course so that it can help students outside the Java study program learn Macapat songs. This research using the R&D Level 1 model, namely researching, producing designs, but not testing and producing them. Validation carried out by Javanese language material experts with a score of 3.7 and validation by design experts received a score of 3.78. Keywords: E Module, Macapat Song Art, MBKM Cross Study Courses